Is Fluoxetine Good for Subacute Stroke? A Meta-Analysis Evidenced From Randomized Controlled Trials - Liu, Guangjie; Yang, Xingyu; Xue, Tao; Chen, Shujun; Wu, Xin; Yan, Zeya; Wang, Zilan; Wu, Da; Chen, Zhouqing; Wang, Zhong (Frontiers in Neurology, 2021)
Background and Purpose：Fluoxetine is a drug commonly used to treat mental disorders such as depression and obsessive-compulsive disorder, and some studies have shown that fluoxetine can improve motor and function recovery after stroke. Therefore, we performed a meta-analysis to investigate the efficacy and safety of fluoxetine in long-term treatment of post-stroke neurological recovery. Methods：PubMed, Embase and Cochrane Library were searched for randomized controlled trials (RCTs) which were performed to assess the efficacy and safety of fluoxetine for functional and motor recovery in acute stroke patients up to October 2020. Review Manager 5.3 software was used to assess the data. The risk ratio (RR) and standard mean difference (SMD) was analyzed and calculated with a fixed effect model. Results：We pooled 6836 patients from 13 RCTs. The primary endpoint was modified Rankin Scale (mRS). Fluoxetine didn’t change the proportion of mRS≤2 (P=0.47). The secondary endpoints were Fugl-Meyer Motor Scale (FMMS), Barthel Index (BI) and National Institute Health Stroke Scale (NIHSS). Fluoxetine improved the FMMS (P＜0.00001) and BI (P＜0.00001) and showed a tendency of improving NIHSS (P=0.08). In addition we found that fluoxetine reduced the rate of new-onset depression (P＜0.0001) and new antidepressants (P＜0.0001), but increased the incidence of fractures (P＜0.0001), hyponatremia (P＝0.01), and seizure (P＝0.03). Conclusion: After acute stroke, fluoxetine did not improve function recovery，but reduced the incidence of post-stroke depression.